A Review of Industrial Internet of Things - Sunil Jhangid, (International Journal of New Media Studies: International Peer Reviewed Scholarly Indexed Journal, 2020)
AI, IIoT, Sensors, ML, VR, AR sort of technologies enables industrial machines, management systems and products to connect to the internet, enabling manufacturers to collect and process data about them for improved efficiency, reliability, flexibility and safety. Additionally, it provides opportunities for automation, predictive maintenance and process optimization. Industry 4.0 and IIoT cyber security can help businesses protect their equipment, data, and systems. By understanding the threats and risks associated with IIoT and Industry 4. 0 systems, organizations can identify,